Impact of intensive upper limb rehabilitation on quality of life: A randomized trial in children with unilateral cerebral palsy - Sakzewski, L.; Carlon, S.; Shields, N.; Ziviani, J.; Ware, R.; Boyd, Roslyn (2012)
Aim The aim of this study was to determine whether constraint-induced movement therapy is more effective than bimanual training in improving the quality of life of children with unilateral cerebral palsy (CP). Method Sixty-three children (mean age 10y 2mo [SD 2y 6mo]; 33 males, 30 females) with CP of the spastic motor type (n=59) or with spasticity and dystonia (n=4) were randomly allocated to two groups. The children were assessed as Manual Ability Classification System level I (n=16), II (n=46), or III (n=1). Each group received 6hours of daily intervention (either constraint-induced movement therapy [CIMT] or bimanual training [BIM]) for 10days over a 2-week period (total intervention time 60h). Children aged 9years and older completed the Cerebral Palsy Quality of Life Questionnaire for Children (CPQOL-Child) and those aged 8years and older completed the KIDSCREEN-52. All parents completed proxy versions of each measure. Assessments were made at baseline and at 3, 26, and 52weeks after the end of the intervention. Results Thirty-five children completed the CPQOL-Child and 41 completed the KIDSCREEN-52. No changes in social or emotional well-being were reported by children in either group. Children and parents from both groups reported a significant improvement in their or their child's feelings about functioning as well as participation and physical health on the CPQOL-Child. The parents of children receiving CIMT reported positive and sustained changes in their child's social well-being (CPQOL-Child). The CIMT group showed significant improvements in physical well-being, psychological well-being, and moods and emotions (KIDSCREEN-52) at 3weeks post intervention, which were maintained over the study period. Interpretation Intensive goal-directed upper limb training programmes using either CIMT or BIM achieved domain-specific changes in quality of life relating to feelings about functioning and participation and physical health. A condition-specific quality of life compared with a generic measure may be better able to detect changes in quality of life in children with unilateral CP. © The Authors. Developmental Medicine & Child Neurology © 2012 Mac Keith Press.